Dynamic minimum dose path-searching method for virtual nuclear facilities. (August 2016) - Li, Meng-kun; Liu, Yong-kuo; Peng, Min-jun; Xie, Chun-li; Wang, Shuang-yu; Chao, Nan; Wen, Zhi-bin
Abstract: Walking path-planning technology can be taken as a radiation protection measure to reduce radiation exposure to workers in radiation environment, and to guarantee work order and efficiency. Considering the nuclear facilities scene can be dynamic and changeable, we designed a dynamic minimum dose walking path-searching method based on the static minimum dose walking path-planning method earlier, and built path-planning simulation platform for nuclear radiation environment with virtual reality technology to plan walking path and virtual simulation. Highlights: Dynamic minimum dose path-searching is proposed. Path-searching method is used for virtual nuclear related environment. Path-planning simulation platform for radiation environment is built.